Mimic and Atavistic Way of Media Policy: the case of Lithuanian Radio and Television - Tillenius, Jurgita (Žurnalistikos tyrimai, 2017)
The post-communist media theorist Karol Jakubowicz distinguished five post-communist media policy theoretical directions. In accordance with these theoretical directions the article analyzes problematic changes of Lithuanian Radio and Television (from 1987 to 1996 – when it was adopted in the first Public Information Act and the Lithuanian National Radio and Television Act) after the collapse of the Soviet totalitarian political system. The downfall of Soviet Union brought major changes in all areas of public life. The media was no exception, but the norm, which is confirmed by the media established theory: the changes of the political regime will inevitably change the prevailed media system. Lithuanian Radio and Television was a tool of the soviet government and the organization had to change a lot after the collapse of Soviet Union. The main aim of article is to analyze which one of the post-communist media policy directions the Lithuanian Radio and Television chose to adopt after the collapse of the Soviet-communist system.